SHARIAH ANALYSIS OF E-COMMERCE TRANSACTIONS FROM THE PERSPECTIVE OF ISLAMIC ECONOMICS - Suci Hayati; Husnul Fatarib (Journal of Social Research, 2022)
Background: Technological developments have had an impact on changes in daily living habits, people who used to shop at traditional markets are now switching to e-commerce because they are considered more effective, efficient and also cheaper. The impact of technological developments extends to Indonesia. This is marked by the proliferation of e-commerce businesses. Objective: The aim is to find out the security and shariah of e-commerce transactions in the perspective of Islamic economics. Therefore, researchers are interested in conducting research with the title "Analysis of the Security and Sharia of E-Commerce Transactions in the Islamic Economic Perspective". Methods: Qualitative research method is a research method based on the philosophy of postpositivism, used to examine the condition of natural objects, (as opposed to experiments) where the researcher is the key instrument, data collection techniques are carried out by triangulation (combined), data analysis is inductive/qualitative , and the results of qualitative research emphasize the meaning of generalization (Sugiyono, 2014). Results: The results of the study show that sharia e-commerce transactions in a sharia economic perspective are the same as buying and selling transactions, which are required to have at least 4 things that must be fulfilled; namely the buyer, the seller, the medium of exchange (money), and the goods being traded or the object of the transaction. Conslusion: Technological developments have had an impact on changes in daily living habits, people who used to shop at traditional markets are now switching to e-commerce because they are considered more effective, efficient and also cheaper. The impact of technological developments extends to Indonesia. This is marked by the proliferation of e-commerce businesses.